AKTIVITAS ANTIOKSIDAN RUMPUT LAUT MERAH (Eucheuma cottonii) DARI PERAIRAN TANJUNGPINANG KEPULAUAN RIAU - Manullang, Benny; Seulalae, Anggrei Viona; Prastari, Cindytia; Rahman , Fathul (Fisheries Product Technology Department, Faculty of Marine Science and Fisheries, Universitas Maritim Raja Ali Haji, 2024)
Indonesia has abundant marine resource potential, including the spread of seaweed across various coastal areas. One area with a great potential is Tanjungpinang. Along the coastline, various types of seaweed have been found, including Eucheuma cottonii, known as red seaweed, which has high economic and ecological value. This study aimed to determine the best treatment for E. cottonii seaweed extract based on yield parameters and antioxidant activity. Samples were extracted using three types of solvents with different polarities, namely ethanol, ethyl acetate, and n-hexane, with a 1:3 (w/v) ratio for each sample. The parameters analyzed included yield, phytochemicals, and antioxidant activity of the DPPH method. The results showed that the yield of E. cottonii powder was 10.34±0.01%. The yield of E. cottonii seaweed extract produced in ethanol, n-hexane, and ethyl acetate was 4 %, 0.40%, and 0.60 %, respectively. E. cottoni extract with ethanol solvent was detected qualitatively to contain alkaloids, flavonoids, phenols, and saponins. The ethyl acetate extract contained alkaloids, phenols, and flavonoids. The n-hexane extract contains alkaloids, flavonoids, and saponins. The ethanol extract had the strongest antioxidant activith (IC50 value of 86.79 ppm, followed by n-hexane (100.76 ppm) and ethyl acetate (114.57 ppm). This study demonstrates the potential of E. cottonii as a source of natural antioxidants.